Estudo da formação e isolamento de heterocomplexos constituídos pela combinação entre 4,4’,4’’,4’’’- tetracarboxiftalocianina de ferro ou 4,4’,4’’,4’’’- tetrassulfoftalocianina de ferro e tetrakis (N-metil- 4-piridil) porfirina de ferro e aplicação em filmes LbL” - Silva, Rebecca Nogueira e (Universidade Federal de São Carlos, 2016)
The great interest in supramolecular assemblies between porphyrins and phthalocyanines has growing lately due to the enhancement on chemical and physical properties compared to individual units. Ionic assemblies with metalloporphyrins and metallophthalocyanines grafted with ionic substituents of opposite charges stand out due to favorable formation and electronic density coupling between the macrocycles rings in a face-to-face array. Most of the reports in the literature on these kinds of arrangements is limited to its solution behavior. The main goal of this work were to synthesize and isolate heterocomplexes of 4,4’,4’’,4’’’- irontetracarboxyphthalocyanine (FeTcPc), or 4,4’,4’’,4’’’- irontetrasulfophthalocyanine (FeTsPc), with irontetrakis(n-metil-4-pyridyl)porphyrin (FeTMPyP). Three tetrapyrrolic macrocycles precursors were synthesized and characterized, and the heterocomplex formation was investigated by spectroscopic titration of FeTMPyP aqueous solution with FeTsPc or FeTcPc. The heterocomplex stoichiometry was determined by Job’s method. The stoichiometry of the heterocomplexes was not affected by the substituents and dyads FeTsPc/FeTMPyP and FeTcPc/FeTMPyP were obtained in both cases. For the first time, dyads were isolated from solution, and characterized by infrared (IR) and ultraviolet-visible (UV-Vis) spectroscopies, thermal analysis, and cyclic voltammetry. A significant change in the macrocycles electronic levels were observed due to the electronic coupling in a face-to- face arrangement. FeTsPc/FeTMPyP dyad presented an extensive orbital mixing, higher than FeTcPc/FeTMPyP dyad. IR analysis showed an additional interaction through coordination of bridged ligand between the metallic centers. Thermogravimetric analysis of the heterocomplexes showed a different degradation profile of the macrocycles in each dyad, which indicated that interaction between the macrocycles in each heterocomplex might be different. Electrostatic Layer-by-Layer technique (LbL) was applied and thin films of macrocycle precursors, mixed films (by intercalating precursor layers), and dyads were obtained. FeTcPc, FeTsPc, and FeTMPyP macrocycles exhibited a linear transfer up to 48 bilayers. The mixed film between FeTsPc and FeTMPyP showed similar spectral properties to FeTsPc/FeTMPyP dyad in solution indicating that similar macrocycles array in the mixed films over the deposition. The cyclic voltammetry of the macrocycles and dyads in solution showed that, in both cases, metallic centers electronic densities were affected by dyad formation, but macrocyclic redox processes was more affected in FeTcPc/FeTMPyP. The immobilization shifted the electrochemical redox process for cathodic potentials. The results indicated that interaction between the macrocycles in the dyads occur via two mechanisms, by ligand bridged interaction between the metallic centers, and by electrostatic attraction of the peripheral substituents.
Formation studies and isolation of heterocomplexes by combinaton of 4,4’,4’’,4’’’-iron tetracarboxyphthalocyanine or 4,4’,4’’,4’’’-iron tetrasulfophthalocyanine with iron tetrakis (n- metil-4-pyridyl) porphyrin and its application in lbl films
Keywords: Porfirina; Ftalocianina; Titulação espectroscópica; Método de Job; Filme fino Layer-by-layer; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA